XXX years of education of physical education teachers in Łódź – a calendar of achievements - Ławniczak, Paweł (Biospołeczne uwarunkowania uczestnictwa w kulturze fizycznej i zdrowotnej osób w różnym wieku, 2017)
The article presents the issues of education of physical education specialists in Łódź. It is an attempt to systematize the achievements in the field of education of physical education teachers, trainers and sports coaches in the academic environment of Łódź.It contains the most important information relating to the origin of access to education at this department, important moments, facts, events decisive for the existence and further education of specialists of physical culture in Łódź. It presents the profiles of the creators of this initiative and important figures in its history.A crucial part of the study are the lists of graduates (Physical and Health Education and Physical Culture and Health), graduating in successive years at the Faculty of Educational Sciences of the University of Łódź.